PROBLEMATICS OF WORKERS LOOK AT COMMERCIAL STILL UNDER THE AGE THAT MUCIKARI SELLS ARE REVIEWED BASED ON LAW NUMBER 35 OF 2014 ABOUT PROTECTION - Darman, Darman (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT              Children as shoots, potential and young generation are the successors of the ideals of the nation's struggle, Children have specific characteristics compared to adults and are one of the vulnerable groups whose rights are still neglected, therefore children's rights are important to prioritize. The formulation of commercial sex workers is one form of crime that is very difficult to deal with and this type of criminality is supported by economic factors in people's lives, where in this society, prostitution cannot be stopped, however, the world of prostitution can at least reveal a lot about the dark side of human life, not only related to sex relations and those involved in it, but also secretly enjoying and taking advantage of the existence of prostitution. Economic needs must be met to continue living. Commercial sex work is their choice. In the community commercial sex workers are seen as not good because they violate the ethics of manners and social norm. Keywords: Pimps and minors